A STUDY ON STABILITY AND IN VIVO DRUG RELEASE OF NAPHAZOLINE AND ANTAZOLINE IN SITU GELLING SYSTEMS FOR OCULAR DELIVERY - G NISHA SHETTY; R.N. CHARYULU (International Journal of Pharma and Bio Sciences, 2013)
This work describes the stability of the selected in situ solutions for ophthalmic delivery of naphazoline hydrochloride ( FF17, FF18) and antazoline phosphate ( GG17 and GG18) based on the pH triggered concept using Carbopol 940 and HPMC K4M. The formulations were evaluated for their pH, isotonicity, gelling capacity, rheological characteristics, in vitro drug release , sterility and in vivo studies in New Zealand rabbits’ eyes. All the formulations showed satisfactory results at ocular pH environment that remains in contact with the eyes for few hours. The formulations were very stable throughout, at room temperature and at 40 °C. Higher amount of both the drugs were retained in the aqueous humour area over 8 hrs following instillation FF17, FF18, GG17& GG18. Therefore, in situ gelling system can be used to enhance the ocular retention time thereby increasing ocular bioavailability and reducing the frequency of dosing .